Structural change and productivity growth in the European Union: Past, present and future - Georg Duernecker; Miguel Sanchez-Martinez (European Commission, Joint Research Centre (JRC), 2021)
The aim of this paper is to investigate the interplay between structural change, interpreted as the secular process of sectoral transformation, and labour productivity growth in the EU in several new dimensions. First, based on the latest data, we document the size of the negative effect that structural change has exerted onto productivity growth over long time horizons. We provide a comparative analysis of these and present-day trends with respect to the US. Second, we develop a general equilibrium model calibrated to match these empirical observations to analyse the potential impact that projected structural change may have on future productivity growth. This model generates structural change through both price and income effects. Our main results indicate that, other things equal, this phenomenon is bound to have a greater dent on productivity growth in the future than it has had in the past. This is the case for both newer and older EU Member States, albeit with important nuances. Our findings suggest that policies should focus on the promotion of productivity-enhancing technological innovation, as well as on the furtherance of greater levels of competition, especially in the most sluggish service sectors.
Keywords: O41; O47; O52; 330; Structural change; Productivity growth; Baumol's cost disease; Service sector; European Union